Infection and higher cortisol during pregnancy and risk for depressive symptoms in adolescent offspring. (July 2022) - Lipner, Emily; Murphy, Shannon K.; Breen, Elizabeth C.; Cohn, Barbara A.; Krigbaum, Nickilou Y.; Cirillo, Piera M.; Alloy, Lauren B.; Ellman, Lauren M.
Abstract: Prenatal infection, particularly at mid-gestation, has been associated with various psychopathological outcomes in offspring; however, findings linking prenatal infection to offspring depression outcomes have been mixed. Previous research indicates that it may be the co-occurrence of prenatal adversities (e.g., infection and stress) that are associated with depression outcomes in offspring. Nevertheless, no study to date has investigated whether higher levels of biomarkers linked to prenatal stress (e.g., cortisol) in the presence of infection may account for these outcomes. Participants were drawn from the Child Health and Development Studies (CHDS), a prospective, longitudinal study of pregnant women and their offspring. The present study included mother-offspring dyads from the Adolescent Study, a subsample of the CHDS cohort, whose offspring were assessed in adolescence and whose mothers also provided sera to be assayed for cortisol (n = 695). Hierarchical multivariable regressions were conducted to examine whether maternal cortisol during the first and second trimesters of pregnancy interacted with maternal infection to predict increased risk for symptoms of depression in adolescent offspring. There was a significant interaction of second trimester infection and higher cortisol on offspring depression scores during adolescence, controlling for maternal education ( p = 0.04). Findings suggest that higher maternal cortisol may sensitize mothers and their offspring to the disruptive influences of infection during mid-pregnancy, conferring greater risk of depressive symptomatology in offspring. Highlights: Co-occurrence of higher cortisol with maternal infection associated with higher depressive symptoms in adolescent offspring. This association is significant only in second trimester. No direct association between higher cortisol or maternal infection with offspring symptoms.